Lysozyme activity of the Ruminococcus champanellensis cellulosome. (7th September 2016) - Moraïs, Sarah; Cockburn, Darrell W.; Ben‐David, Yonit; Koropatkin, Nicole M.; Martens, Eric C.; Duncan, Sylvia H.; Flint, Harry J.; Mizrahi, Itzhak; Bayer, Edward A.
Summary: Ruminococcus champanellensis is a keystone species in the human gut that produces an intricate cellulosome system of various architectures. A variety of cellulosomal enzymes have been identified, which exhibit a range of hydrolytic activities on lignocellulosic substrates. We describe herein a unique R. champanellensis scaffoldin, ScaK, which is expressed during growth on cellobiose and comprises a cohesin module and a family 25 glycoside hydrolase (GH25). The GH25 is non‐autolytic and exhibits lysozyme‐mediated lytic activity against several bacterial species. Despite the narrow acidic pH curve, the enzyme is active along a temperature range from 2 to 85°C and is stable at very high temperatures for extended incubation periods. The ScaK cohesin was shown to bind selectively to the dockerin of a monovalent scaffoldin (ScaG), thus enabling formation of a cell‐free cellulosome, whereby ScaG interacts with a divalent scaffodin (ScaA) that bears the enzymes either directly or through additional monovalent scaffoldins (ScaC and ScaD). The ScaK cohesin also interacts with the dockerin of a protein comprising multiple Fn3 domains that can potentially promote adhesion to carbohydrates and the bacterial cell surface. A cell‐free cellulosomal GH25 lysozyme may provide a bacterial strategy to both hydrolyze lignocellulose and repel eventual food competitors and/or cheaters.